Efficacy of Atezolizumab for Advanced Non-Small Cell Lung Cancer Based on Clinical and Molecular Features: A Meta-Analysis - Liu, Wenjie; Huo, Gengwei; Chen, Peng (Frontiers in Immunology, 2022)
Objective: Atezolizumab is becoming a significant therapy for NSCLC, but its efficacy needs to be further improved. To clarify the potency of atezolizumab-based therapy in advanced NSCLC patients with different clinical and molecular features, to choose a better therapeutic regimen of atezolizumab to achieve more precise treatment in immunotherapy. Methods: Randomized clinical trials (RCTs) in the Cochrane Library, PubMed, Embase Science Direct, and Google Scholar, together with major oncology conferences that compared atezolizumab with chemotherapy-based treatment for individuals with advanced NSCLC published prior to February 2022, were searched. Studies, bias risk assessment, and data extraction were selected by two independent authors. We extracted the basic features of the included studies, together with the 95% CI and hazard ratios (HR), from all patients and subgroups. The combined treatment data were assessed using the inverse variance weighting method. Results: Seven RCTs including 4,859 patients were included. Our meta-analysis findings indicated that atezolizumab substantially enhanced OS (HR 0.82; CI95%, 0.77-0.88; P <0.00001) and PFS (HR 0.72; CI95%, 0.61-0.85; P <0.0001) in patients with advanced NSCLC compared with chemotherapy-based treatment. Substantially enhanced OS in patients aged <65 years old, 65-74 years old, wild-type EGFR, without liver metastases, active or previous smokers, whites, TC3 or IC3, TC2/3 or IC2/3, TC1/2/3 or IC1/2/3, and TC0 and IC0, but not in patients aged ≥75 years, never smokers, liver metastases, EGFR mutant, Asians, Blacks or African Americans, or TC1/2 or IC1/2. Patients with advanced NSCLC who received atezolizumab showed OS improvement regardless of sex (male or female), histological type (non-squamous or squamous NSCLC), performance status (0 or 1), and line of treatment (1st-line therapy or ≥2nd-line therapy). Subgroup analysis revealed that individuals with male sex, non-squamous NSCLC, PS 1, active or previous smokers, wild-type EGFR, TC3 or IC3, and TC1/2/3 or IC1/2/3 achieved OS benefit from atezolizumab treatment not related to the treatment line and treatment regimen. Conclusions: Age group, smoking history, liver metastasis status, EGFR mutation status, race, and PD-L1 expression can be used to predict the potency of atezolizumab and provide a better treatment regimen for patients with advanced NSCLC to achieve accurate and personalized treatment.